2013
DOI: 10.1080/13825585.2013.789096
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inhibitory processes on affective theory of mind in young and old adults

Abstract: The primary aim of this study was to examine the impact of an inhibition manipulation on the effect of age on theory of mind (ToM) in an ecologically valid, affective ToM task. Participants were 30 young and 30 old adults. The Cambridge Mindreading Face-Voice Battery was used to measure ToM; in addition, measures of fluid and crystallized intelligence were taken. Participants were subjected to three levels of inhibitory demand during ToM reasoning: emotional inhibition, non-emotional inhibition, and no inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
4
26
1
1
Order By: Relevance
“…On affective ToM, we found that EF abilities were not related to performance, which is in line with most previous aging studies (Bottiroli et al, 2016;Duval et al, 2011;Keightley et al, 2006;Mahy et al, 2014;Sullivan & Ruffman, 2004;Wang & Su, 2013). However, Johansson Nolaker et al (2018) found that updating, gender and cognitive empathy explained associated with age-related changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On affective ToM, we found that EF abilities were not related to performance, which is in line with most previous aging studies (Bottiroli et al, 2016;Duval et al, 2011;Keightley et al, 2006;Mahy et al, 2014;Sullivan & Ruffman, 2004;Wang & Su, 2013). However, Johansson Nolaker et al (2018) found that updating, gender and cognitive empathy explained associated with age-related changes.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Bernstein et al (2011) showed that age, but not EF abilities, significantly contributed to variance on a continuous false-belief task. On affective ToM, performance on the RME was not related to age-related declines in inhibition, set-shifting or updating (Duval, Piolino, Bejanin, Eustache, & Desgranges, 2011) and there were no age-related differences in inhibitory control on the Cambridge Mindreading Face-Voice Battery (Mahy et al, 2014). Other studies have also failed to show that age-related declines in affective ToM are explained by EF performance (Keightley et al, 2006;Sullivan & Ruffman, 2004;Wang & Su, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…As hypothesized, inhibitory top-down control and affective ToM shared some variance (Bull et al, 2008;Mahy et al, 2014;Wang et al, 2015), and the association between affective ToM and hallucinatory behavior seemed to be mediated by poor inhibitory top-down control (Lam et al, 2014). This shared portion of variance might represent more elementary cognitive features such as monitoring skills, which might underlie both functions.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, a dual-task experiment of Bull et al (2008) in which reduced affective ToM performance during an inhibition task was observed suggested even greater involvement of inhibitory control in affective compared to cognitive ToM. The authors claimed that good performance on the Reading the Mind in the Eyes Test may require inhibition of social and personal features (e.g., gender, age, facial features) attributed to the faces (see also Mahy et al, 2014). Since the occurrence of hallucinations was additionally associated with impaired inhibitory top-down control (Bozikas et al, 2014;Ford and Mathalon, 2004;Hugdahl et al, 2013) the current study aimed to investigate the connections between auditory inhibition, affective ToM and the experience of hallucinations in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 95%
“…Рассогла-сование собственных представлений и представлений других людей может приводить к недопониманию, развитию конфликтов и нарушению социально-го взаимодействия, что способствует увеличению психосоциальных проблем в позднем возрасте. Эти трудности мо-гут приводить к снижению социальной активности, дистанцированию от кру-га значимых людей, усиливая чувство одиночества, невостребованности, чем способствуют развитию соматических и аффективных расстройств (например, депрессии позднего возраста) с последу-ющим ухудшением состояния здоровья вплоть до инвалидизации [23].…”
Section: экспериментальные исследованияunclassified